A comparative study on the performance of biodiesel in a modern 1.9L turbo diesel engine - Kotze, Johan (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScEng (Mechanical and Mechatronic Engineering))--University of Stellenbosch, 2010.